Ritual Mosebi pada masyarakat Tolaki - Rilda Yanti; Zainal Zainal (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
This study aims to determine and describe the community’s interpretation of Mosebi rituals and their social impact on the community in Wanggudu Village, Asera District, North Konawe Regency. In this study, Victor Turner’s ritual theory was used by using ethnographic methods. The result of the study show that mosebi is a ritual to resolve the case of a married wifw’s infidelit. Before the mosebi ritual is carried out, there are several rituals that must be perfomed first, including the mombesara ritual (handing over the traditional principal) and the mosehe ritual (purifying the din). The mosebi ritual only enforced for a womwn who is already married but dioes not apply to a man who already has a wife the process of carrying out. The mosebi ritual in wanggudu village, asera district, north konawe regency. Is carried out without presenting the perpetrator of the affair. But instead they are represented by each family to avoid chaos. For that key use a cow that is used as a sacrifice to replace the kasuworoko (the neck of the two partners who have had an affair or umoapi.